Incidence of methicillin resistant Staphylococcus aureus (MRSA) in burn intensive care unit: a systematic review - Khan, Tahir Mehmood; Kok, Yee Leng; Bukhsh, Allah; Lee, Learn Han; Chan, Kok Gan; Goh, Bey Hing (European Academy of HIV/AIDS and Infectious Diseases, 2018)
Background Burn victims admitted in burn intensive care units (ICU) are at a high risk of nosocomial infections generated by methicillin resistant Staphylococcus aureus (MRSA). This systematic review aims to estimate the incidence of MRSA among burn patients admitted to the ICU setting, with an emphasis on the incidence rate and antibiotic resistance profile of the MRSA strains. Methods A systematic literature search was performed in five electronic databases limited to publication dates from 1 st January 2000 until 31 st August 2017. After screening n=481 articles, n=21 were found to meet the inclusion criteria of this systematic review. Results Results from the meta-analysis revealed that the risk for MRSA isolates in the burn ICU was 55.0% higher (OR 0.55, 95%CI 0.32-0.94). Therefore, timely testing, appropriate hygiene practice and suggested wound care must be practiced while handling such patients. Conclusion Further studies are needed to identify the risk factors of MRSA infections among burn patients and to develop new antimicrobial agents for MRSA infections.